AD, Volume 19, n° 4, 1994 - Full Issue - Journal System (Africa Development, 1994)
Contents Introduction Sibry Tapsoba ....................................... 5 Education des filles: Quelles perspectives pour l'Afrique subsaharienne au XXI e siècle? Alphonsine Bouya .............................. 11 Education and Social Reconstruction:The Case of South Africa Neville Alexander ............................. 35 Gender Issues in Contemporary African Education Florence Ebam Etta ................................ 57 Education de base et participation communautaire en Afrique subsaharienne: Réflexions sur l'orientation de la recherche Sibry Tapsoba ................................ 85 Financing Education in Africa: Need for Improved Aid Coordination Linda English .................................. 97 Educational Research and Policy Analysis Capacity for Educational Change in sub-Saharan Africa Kabiru Kinyanjui ...........................113 Illiteracy, Education and National Development in Postcolonial West Africa: A Re-Appraisal Hubert Oswald Quist ...................... 127 Réformes éducatives et développement en Afrique subsaharienne: Pour une vision partagée Medjomo Coulihaly ............................147 Diagnostic du système éducatif béninois: Eléments pour une réforme novatrice des systèmes éducatifs africains Dénis Amoussou-Yeye .......................... 165 Review Essay African Studies and the Disintegration of Paradigms Paul Tîyambe Zeleza .......................... 179 Bibliography ........................... 195